Expectations of Korean Nursing Students Regarding the Enactment of Nursing Law - Kang, Se-Won (Advances in Social Sciences Research Journal, 2024)
This descriptive survey aimed to determine Korean nursing students’ expectations regarding enacting the nursing law. The participants were 150 nursing students. Data were collected from October 1 to October 15, 2024. The average score for expectations and perceptions regarding the enactment of nursing law was 4.42 points (out of 5 points). The item with the highest score was: ’The roles and scope of work of specialized nurses in each field will be clearer, which will help establish a specialized nurse system." The Korean Nursing Law has taken its initial steps. However, further discussion and development are necessary to safeguard nurses’ rights and ensure patient safety.